(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2024)
This article is a creative, written in a more motivational spirit to benefit the youth. Everyone reading the article is aimed at strengthening your sense of confidence. Excerpts from the lives of famous people, useful advise, and various quotes are also mentioned.